REGIONAL SUBJECT COMPETITION: PRACTICAL EXPERIENCE - Zulfiya F. Zaripova (Высшее образование в России)
The current socio-economic situation in the region calls for the high intellectual level of future oil and gas engineers. The Institute and the leading oil company in the region are interested in search and selection of the talented youth as a future human resource. Therefore since 2011 they organize the regional subject competition for pupils. This paper analyzes the possibilities of the contest environment for self-development of future students.